Reading medieval culture: essays in honor of Robert W. Hanning - Stein, Robert M.; Hanning, Robert W. (Univ. of Notre Dame Press, 2005)
From Bede's world to "Bede's world" / Nicholas Howe -- Prolixitas temporum : futurity in medieval historical narratives / Monika Otter -- What's love got to do with it? : Abbot Suger and the renovation of St. Denis / Sarah Spence -- Time and nature in twelfth-century thought : William of Conches, Thierry of Chartres, and the "new science" / Charlotte Gross -- Christina of Markyate and Theodora of Huntingdon : narrative careers / Nancy F. Partner -- The voice of the hind : the emergence of feminine discontent in the lais of Marie de France / H. Marshall Leicester -- Troy, Arthur, and the languages of "Brutis Albyoun" / Christopher Baswell -- The hunger for national identity in Richard Coer de Lion / Suzanne Conklin Akbari -- The body of the nun's priest, or, Chaucer's disseminal genius / Peter W. Travis -- "Leve brother" : fraternalism and craft identity in the miller's prologue and tale / Margaret Pappano -- All that glisters : the historical setting of the tale of Sir Thopas / William Askins -- Chaucer and Langland : a fellowship of makers / George D. Economou -- "Raptus" and the poetics of married love in Chaucer's wife of Bath's tale and James I's Kingis quair / Elizabeth Robertson -- Chaucer's Criseyde : the betrayer betrayed / Laura L. Howes -- Chaucer and free love / John M. Ganim -- Professionalizing Chaucer : John Matthews Manly, Edith Rickert, and The Canterbury tales as cultural capital / Sealy Gilles and Sylvia Tomasch -- Gli scogli neri ed il niente che c'è : Dorigen's black rocks and Chaucer's translation of Italy / Warren Ginsberg --